711 POST-REFLUX SWALLOW-INDUCED PERISTALTIC WAVE IS IMPAIRED IN LARYNGOPHARYNGEAL AND GASTRO-OESOPHAGEAL REFLUX DISEASE. (17th September 2021) - Park, Jin-soo; Van der Wall, Hans; Falk, Gregory
Abstract:  : Laryngopharyngeal reflux (LPR) and gastro-oesophageal reflux disease (GORD) result from the reflux of gastric contents. The post-reflux swallow-induced peristaltic wave (PSPW) induces chemical clearance following reflux events. PSPW index is a novel parameter that has been validated in GORD, but not in LPR. This study aimed to assess the efficacy of chemical clearance by assessing PSPW indices in patients with LPR and GORD. Methods: Reviewers blindly analysed off-therapy impedance-pH tracings from 187 patients divided into LPR (n = 105) or GORD (n = 82) by predominant symptom profile. Conventional impedance-pH measures and PSPW indices were analysed for the two groups. Results: Mean PSPW index in the LPR group was higher than in the GORD group (39.7% (±17.7%) vs. 20.6% (±13.4%); p < 0.001). Abnormally low PSPW index (<61%) was seen in 85 (81%) of the LPR group, and 80 (97.6%) of the GORD group (p < 0.001). Area under the ROC curve for PSPW index to diagnose LPR was 0.828 (95% CI: 0.767–0.889; p < 0.001). The LPR group had a lower AET (1.5% vs. 8.1%; p < 0.001) and fewer distal reflux episodes (46.5 (±24.5) vs. 64.4 (±39); p < 0.001). Conclusion: PSPW was impaired in patients with LPR as well as oesophageal GORD, indicating an abnormality of chemical clearance following a reflux episode in both groups. PSPW index was more severely impaired in gastro-oesophageal reflux disease (GORD). The present study shows PSPW index is useful in aiding in the diagnosis of both LPR and GORD.